Expression of a flower-specific Myb protein in leaf cells using a viral vector causes ectopic activation of a target promoter. - Sablowski, R W (1995)
The promoter of the bean PAL2 gene (encoding phenylalanine ammonia-lyase; EC 4.3.1.5) is a model for studies of tissue-restricted gene expression in plants. Petal epidermis is one of the tissues in which this promoter is activated in tobacco. Previous work suggested that a major factor establishing the pattern of PAL2 expression in tobacco petals is the tissue distribution of a protein closely related to Myb305, which is a Myb-like transcriptional activator from snapdragon. In the present work, we show that Myb305 expression in tobacco leaves causes ectopic activation of the PAL2 promoter. To achieve Myb305 expression in planta, a viral expression vector was used. This approach combines the utility of transient assays with the possibility of direct biochemical detection of the introduced factor and may have wider application for studying the function of plant transcription factors.